QUALITY OF LIFE AMONG OUTPATIENTS WITH CERVICAL BRACHIAL SYNDROME AT THE NATIONAL HOSPITAL OF ACUPUNCTURE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the quality of life and identify factors associated with quality of life among outpatients with cervical brachial syndrome at the National Hospital of Acupuncture in 2025.Methods: A cross-sectional descriptive study was conducted on 115 outpatients aged 18 years and older who were diagnosed with cervical brachial syndrome and received outpatient treatment at the National Hospital of Acupuncture from March to October 2025. Data were collected through face-to-face interviews using a structured questionnaire and supplemented by medical record review. Pain intensity was assessed using the Visual Analogue Scale (VAS), daily functional limitation was evaluated using the Neck Disability Index (NDI), and quality of life was assessed using the SF-12 questionnaire.Results: The mean age of participants was 49 ± 12 years; females accounted for 69.6%, and the 40–49 age group represented the largest proportion. Moderate and severe pain accounted for 48.7% and 27.0%, respectively. Moderate and severe limitation in cervical range of motion were observed in 67.0% and 21.7% of participants, respectively. According to the NDI, 45.2% of patients had severe disability and 40.9% had moderate disability. The mean scores for the physical health component, mental health component, and overall quality of life were 45.3 ± 29.1, 38.4 ± 26.4, and 41.9 ± 26.9, respectively. Univariate analyses showed that age, sex, occupation, economic status, spinal lesion characteristics, number of treatment episodes, and delay from symptom onset to hospital visit were associated with quality of life (p < 0.05).Conclusion: Quality of life among outpatients with cervical brachial syndrome at the National Hospital of Acupuncture was at a moderately low level, with mental health being more affected than physical health. Several personal and clinical factors were associated with quality of life. These findings may help guide counseling, follow-up, and supportive care for patients at higher risk of poor quality of life.
Keywords: Cervical brachial syndrome, quality of life, SF-12, VAS, NDI, associated factors.